Cultural resistance and negotiation in video game Pamali: Indonesian folklore horror - The Tied Corpse - Setyawan, Rakha; Sajarwa, Sajarwa; Sutrisno, Adi (Diksi, 2023)
Localization of video games makes it easier for players with different language settings to play foreign games. However, a few games customized their game with cultural terms that may confuse the player. This research aimed to examine (1) cultural resistance and negotiation terms, (2) and the subtitling strategy translation on the game Pamali: Indonesian Folklore Horror - The Tied Corpse by StoryTale Studios. The data sources were extracted from words, phrases, and sentences from the game subtitles in Indonesian and English versions. Document observation was used as the data collection technique, meanwhile content analysis was used as the data analysis technique. Cultural-related term classification data were analyzed using the combined taxonomic theory of cultural-term from (Newmark, 1988; Tomalin and Stempleski, 2013; Zare-Behtash and Firoozkoohi, 2013). Gottlieb's (1994) subtitle translation strategy was used by the researcher to identifiy the translation process. The result shows six resisted data in three cultural-term categories; Dialect, Ideas; Beliefs. On the other hand, forty-one negotiated data were found in ten cultural-related categories; Ideas; beliefs, Concept; religion, Dialect, Gesture and Habit, Ecology, Idiom, House and Towns, Artefact, Date, and Antrophonym. The Imitation subtitling strategy is found in the resisted data. Meanwhile, the negosiated data applied the Transfer, Transcription, Expansion, Paraphrase, and Deletion subtitling strategy. The negotiation strategy was applied more than the resistance to commercially make the video game accessible to the international player.Keywords: resistance and negotiation, cultural-related term, subtitles, Pamali: Indonesian folklore horror - The tied corpse